Field induced hysteretic structural phase switching and possible CDW in Re-doped MoTe2. (21st May 2021) - Vasdev, Aastha; Kamboj, Suman; Sirohi, Anshu; Mandal, Manasi; Marik, Sourav; Singh, Ravi Prakash; Sheet, Goutam
Abstract: Novel electronic systems displaying exotic physical properties can be derived from complex topological materials through chemical doping. MoTe2, the candidate type-II Weyl semimetal shows dramatically enhanced superconductivity up to 4.1 K upon Re doping in Mo sites. Based on bulk transport and local scanning tunnelling microscopy here we show that Re doping also leads to the emergence of a possible charge density wave phase in Re0.2 Mo0.8 Te2 . In addition, the tunnelling I – V characteristics display non-linearity and hysteresis which is commensurate with a hysteresis observed in the change in tip-height ( z ) as a function of applied voltage V . The observations indicate an electric field induced hysteretic switching consistent with piezoelectricity and possible ferroelectricity.